(con)temporary space: conceiving open space in Nyhamnen — Malmö - Henriksson, Alexander (2015)
This Master thesis is, in a sense, a continuation and expansion of my Bachelor thesis. The Bachelor thesis was focused on analysing and discussing how landscape architects weigh different factors against each other in a design situation. This thesis is instead focused on actual on-site and trans-areal site exploration using a specified method chosen through a formulated theoretical standpoint and by using the harbour area of Nyhamnen in Malmö as a chosen site. The main theoretical contributors are Andrea Kahn and Carol Burns for their definition of site as a dynamic relational construct (2005), Lisa Diedrich’s PhD thesis on site-specificity and harbour transformation (2013), the geographer Doreen Massey for her theory on space and place (2005), the land artist Robert Smithson (here analysed by Nick Kaye) with his thoughts on site and non-site (Kaye 2000), and the French art-theoretician Nicolas Bourriaud for his theories on the characteristics of the alter-modern, what he proposes is our current time (2009). The chosen design method for the thesis is that of the deviant transect, an experiment originally constructed by the researchers Ellen Braae, Lisa Diedrich and Gini Lee (2014). The method of the deviant transect aims to combine pre-gained site knowledge with actual trans-areal site exploration, and in so doing reveal previously unseen or perhaps overlooked material or immaterial information and relations. The deviant transect carried out in Nyhamnen and its surrounds investigates and explores the spaces and places of the area and looks for material, dynamic and relational aspects. The findings from the transects are presented using a series of maps and images divided into the two themes transitional waterscapes and emerging foodscapes. The thesis aims to, on one hand, analyse Nyhamnen and make a contribution to the already ongoing discussion about the area, but on the other hand also to explore possible ways of apprehending and understanding urban sites using Nyhamnen as a test subject. Therefore it does not aim to create an all encompassing design solution for the coming development of Nyhamnen or a design solution for a certain part, but rather to highlight or pinpoint aspects which could serve as a starting point for site specific design in Nyhamnen or as a way of showing what the open space in Nyhamnen could be conceived as.